Nascent RNA sequencing reveals mechanisms of gene regulation in the human malaria parasite Plasmodium falciparum - Lu, Xueqing Maggie; Batugedara, Gayani; Lee, Michael; Prudhomme, Jacques; Bunnik, Evelien M.; Le Roch, Karine G. (Nucleic acids research, 2017)
Gene expression in Plasmodium falciparum is tightly regulated to ensure successful propagation of the parasite throughout its complex life cycle. The earliest transcriptomics studies in P. falciparum suggested a cascade of transcriptional activity over the course of the 48-hour intraerythrocytic developmental cycle (IDC); however, the just-in-time transcriptional model has recently been challenged by findings that show the importance of post-transcriptional regulation. To further explore the role of transcriptional regulation, we performed the first genome-wide nascent RNA profiling in P. falciparum. Our findings indicate that the majority of genes are transcribed simultaneously during the trophozoite stage of the IDC and that only a small subset of genes is subject to differential transcriptional timing. RNA polymerase II is engaged with promoter regions prior to this transcriptional burst, suggesting that Pol II pausing plays a dominant role in gene regulation. In addition, we found that the overall transcriptional program during gametocyte differentiation is surprisingly similar to the IDC, with the exception of relatively small subsets of genes. Results from this study suggest that further characterization of the molecular players that regulate stage-specific gene expression and Pol II pausing will contribute to our continuous search for novel antimalarial drug targets.